KHRINNYKY RESERVOIR AS AN ESSENTIAL ELEMENT OF THE RIVER STYR WATER ECOSYSTEM - Kopylova, Olha; Voznіuk Nataliia; Likho, Olena (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
The article deals with the positive and negative effects of reservoirs functioning as integral elements of rivers water ecosystems. There are 12 reservoirs operating in the Rivne region with overall volume of 47.8 million m3. Khrinnyky reservoir on the river Styr is one of the largest reservoirs with a volume exceeding 10 million m3. It was built in 1957 in order to provide the embedded in the dam body hydroelectric power plant with 960 kW capacity, as well as for recreational and fishery purposes. The reservoir area is 1830 hectares, the depth varies from 2 to 6 meters, in the pits and river beds – up to nine. During the period of its existence, the reservoir has been activated several times. Since the water of Khrinnyky reservoir is used by a significant part of the population for fishery, household and recreational needs, the quality of the water environment has been analyzed on the basis of laboratory control results. Comparison of the available hydrochemical data on the surface water quality of the Khrinnyky reservoir with the maximum permissible concentration is not relevant, however, at that time the excess was recorded by such indicators as BOD5, iron, zinc. Analysis of the research results suggests that the reservoir has a significant positive impact on the quality of water in the water courses on which they are created, primarily due to sedimentation processes. It should be noted that the Khrinnyky reservoir, after water discharge, was filled with water without first removing the residues of higher aquatic vegetation with the dominance of tall –growing helophytes. As a result, specific hydrochemical and hydrobiological conditions were formed and, for several years afterwards, the breath of hydrobionts was observed in the summer due to the decay of the flooded biomass. In order to ensure a favorable status of the water environment of the Khrinnyky reservoir in modern conditions, it is necessary to regulate recreational activities and management with in the water protection zone and the coastal strip. Assessment of water quality, analysis of sediment status is the primary ask of monitoring the status of reservoirs and their impact on rivers.